Christmas at Carnton - Alexander, Tamera (Thorndike, Maine : Center Point Large Print, 2017)
"Amid war and the fading dream of the Confederacy, a wounded soldier and a destitute widow discover the true meaning of Christmas--and of sacrificial love. Set against the backdrop and history of the Carnton Plantation in Franklin, Tennessee"--
Keywords: Large type books; Christmas stories; Historical fiction; Love stories; Christian fiction